Metro Manila Urban Transportation Strategy Planning Project, institutional development implementation report, vol. 5, part b1 implementation ;project prioritization, refinement and adoption (Pak-Poy & Kneebone Pty Ltd, 1986)
This volume contains technical memoranda related Institutional Development prepared as part of the Metro Manila Urban Transportation Strategy Planning Project (MMUTSTRAP) Part B1 - Implementation Phase.